2008
DOI: 10.1080/15374410802148186
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Symptoms and Somatic Complaints Following Hurricane Katrina: The Roles of Trait Anxiety and Anxiety Sensitivity

Abstract: This study examined the relationships between trait anxiety and anxiety sensitivity and the outcome variables posttraumatic stress disorder (PTSD) symptoms and somatic complaints following a major hurricane. Sixth and seventh graders in the New Orleans area (N = 302) were surveyed 5 to 8 months following Hurricane Katrina. As expected, hurricane exposure was a significant predictor of PTSD symptoms and somatic symptoms. Also as hypothesized, certain factors of anxiety sensitivity interacted with trait anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
97
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 46 publications
13
97
1
Order By: Relevance
“…However, when we compared those who completed the study versus those who dropped out, we found no significant differences. Further, while the percent of participants who reported a perceived life threatening experience during the hurricane was similar to previous research (Hensley & Varela, 2008), the mean reported actual life threatening experiences was low in this sample. The low exposure in this sample may indicate that their exposure was peripheral.…”
Section: Discussionsupporting
confidence: 87%
“…However, when we compared those who completed the study versus those who dropped out, we found no significant differences. Further, while the percent of participants who reported a perceived life threatening experience during the hurricane was similar to previous research (Hensley & Varela, 2008), the mean reported actual life threatening experiences was low in this sample. The low exposure in this sample may indicate that their exposure was peripheral.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, somatic complaints, such as feeling dizzy or lightheaded, overtired without good reason, and physical problems without a known medical cause, proved correlated to PSB persistence. These complaints have been reported in children who manifest various other difficulties, including suicidal ideation, attempted suicide, internalizing disorders, posttraumatic stress disorder, and maltreatment, especially sexual abuse (Ginsburg, Riddle, & Davies, 2006;Haugaard, 2004;Hensley & Varela, 2008;Hukkanen, Sourander, & Bergroth, 2003;Van Tilburg et al, 2010), but not in children with PSB. Regarding maltreatment, our results suggest that it does not predict the persistence of PSB.…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 Regardless of whether studies examine exposure as a composite measure that combines life threat, loss, and exposure to destruction 16,17 or whether studies examine these dimensions of exposure separately 18 findings across studies indicate a clear dose-response relationship: As exposure across these dimensions increases, emotional distress increases. This study showed that 47.6% of Palestinian children were considered as PTSD.…”
Section: Discussionmentioning
confidence: 99%